(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2025)
Do refugees affect the outbreak of social conflict in the host country? If so, how do refugees influence the rise of domestic conflict? Prior scholarship demonstrated that there is a significant relationship between refugees in a host country and civil conflict; however, the focus on high battlefield death counts overlooks the potential relationship between the introduction of refugees in a host country and the rise of social conflict. We argue that the migration of refugees can increase the number of social conflict events within the host country by potentially increasing the ethnic-religious composition of the host country, increasing the economic competition by the availability of labor and altering governmental spending, and introducing a new population with complex grievances. Using a negative binomial model to test the relationship on a sample of African and Caribbean countries, we find support for our contention. While refugees are seeking security within a host country, the increase in refugees triggers a negative perception within society concerning them and consequently increases the propensity of social conflict. The development of social conflict can be significantly moderated through the further support and increased funding for refugees and host countries by developed countries.